Feedlot and carcass studies on Sirohi, Marwari and Kutchi kids with economics of production under intensive system of management - MEHTA, B S; KHAN, B L; TOMAR, A K S (The Indian Journal of Animal Sciences, 2013)
Data pertaining to 63 male kids belonging to Sirohi, Marwari and Kutchi goat breeds under feedlot experiment (for a period of 3-12 months of age), planned in intensive system of management during 1992-93 with a ration consisting of concentrate and roughage in a ratio oUiO: 40 revealed that initial body weights (at 3 months of age) were 15.70±0.51 (Sirohi), 14.56±0.32 (Marwari) and 14.00±0.58 kg (Kutchi). The final live body weights (at 9 months) at slaughter age were 37 .33± 1.17 (Sirohi), 34.81±0.47 (Mar,vari) and 32.76±1.44 kg (Kutchi). The live body weights at 12 months of age for rest of the kids were 45.15±1.02 (Sirohi). 41.25±0. 72 (Marwari) and 40.38:1:1.54 kg (Kutchi). The ranges for average daily gains during phase-l (3-6 months), 2 (6-9 months) and 3 (9-12 months) were 106 (Kutchi) to 134.09 g (Marwari), 90.45 (Marwari) to 115.9 g (Sirohi) and 65.83 (Kutchi) to 80.7 g (Sirohi), respectively. Ranges for dry matter intake/kg live body weight gain during phases-1, 2, 3 and 4 were 6.19 (Marwari) to 7.29 kg (Kutchi); 9.36 (Kutchi) to 10.64 kg (Marwari); 14.41 (Sirohi) to 16.83 kg (Marwari) and 8.90 (Kutchi) to 9.52 kg (Marwari) respectively. Slaughter studies indicated that dressing percentages on the basis of pre-slaughter weights were 48.9 1 (Sirohi), 48.46 (Marwari) and 52.06% (Kutchi). Other carcass traits and economics of meat production were also studied and reported in the text.